Respuesta :

Answer:

t1 = 14  d= -2

Step-by-step explanation:

tn = t1 + d ( n-1)

t6 = t1 + d(6-1)

4 = t1+ 5d

t10 = t1 +d (10-1)

-4 = t1 +d9

Take the two equations and subtract to eliminate a1

4 = t1+ 5d

- (-4 = t1 +d9)

-------------------------

4 = t1+ 5d

+4 =- t1 -d9

-------------------------

8  =   -4d

Divide each side by -4

8/-4 = -4d/-4

-2 =d

Now we can find t1

4 = t1+ 5d

4 = t1 + 5(-2)

4 = t1 -10

Add 10 to each side

4+10 = t1

14 = t1

Answer:

A

Step-by-step explanation:

t1 = a

tn = a + (n-1)d

t6 = a + 5d = 4

a = 4 - 5d

t10 = a + 9d = -4

4 - 5d + 9d = -4

-8 = 4d

d = -2

a = 4 - 5(-2)

= 4 + 10

= 14

ACCESS MORE